THE EFFECTS VERY LOW CARBOHYDRATE DIET (VLCBD) ON RENAL OUTCOMES IN DIABETIC KIDNEY DISEASE PATIENTS: A 12-WEEK RANDOMIZED CONTROLLED TRIAL - Zainordin, Nur Aisyah; Warman, Nur Aini Eddy; Mohamad, Aimi Fadhilah; Yazid, Fatin Aqilah Abu; Ismail, Nazrul Hadi; Wee, Chen Xin; Rahman, Thuhairah Hasrah Abd; Koshy, Marymol; Razalli, Mazuin Mohd; Ghani, Rohana Abd (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Dietary modality such as very low carbohydrate diets (VLCBD) is an effective means to reduce weight and blood pressure, with subsequently improved glycaemic control and reduced hyperfiltration in DKD. The objectives of the randomized controlled trial study are to assess the improvement of VLCBD in addition to a low protein diet (LPD) on renal outcomes and metabolic parameters in DKD patients. METHODOLOGY This was an investigator-initiated, single-center, randomized, controlled, open-labeled, clinical trial in T2DM patients with DKD, comparing 12-weeks of low carbohydrate diet (<20g daily intake) versus standard low protein (0.8g/kg/day) and low salt diet. Patients with type 2 diabetes aged 40-75 years and an HbA1c 7-10.5% were randomized. The main outcomes were changes in proteinuria assessed by UPCR and urine microalbumin and a rise in serum creatine with reduction in eGFR. RESULTS A total of 30 participants were enrolled (median (IQR) age 57 (11), BMI 30.68 (8.38), and HbA1c 8.8 (1.7)). VLCBD groups achieved significant lower total carbohydrate intake at week 12 in comparison to LPD group (27(25) g vs 89.33(77.4)g, p= < 0.01). No difference between the groups were found in change in UPCR, urine microalbumin, creatinine, eGFR and blood pressure. The VLCBD group demonstrated significant reductions in weight (-4.0 IQR 3.9 vs 0.2 IQR4.2 kg, p=<0.001) and BMI (-1.5 IQR 1.18 vs 0.074 IQR 1.54) which were not seen within the LPD group. There was reduction in HbA1c (1.3 IQR1.1 % vs 0.7 IQR1.25 %, respectively, p=NS) and fasting blood glucose in both groups. Both dietary interventions were well received with no reported adverse events. CONCLUSION The result suggests that the intervention of very low carbohydrate diet, in patients with underlying diabetic kidney disease was safe in preserving renal functions with improvement in weight and glycaemic control within 12 weeks of interventions.